Reaching internal consensus: Decision-making by transgender and plural people - Silver Mckie; Sana Flynn; Christopher Wolf-Gould; Susan C. Turell; Matthew A. Adan; The Redwoods (PLoS ONE, 2025)
People who identify as both transgender and plural (more than one person sharing a body), including those with a diagnosis of Dissociative Identity Disorder, make decisions related to gender identity and presentation, and may engage with healthcare providers to receive gender affirming care. Internal decision-making by people experiencing plurality has not been studied extensively. Furthermore, the existing literature on plural decision-making does not address the intersection of transgender identity and the associated choices to be made about external gender expression or shared body modifications. Using a community-based participatory research design and a non-pathologizing lens, the research team interviewed 15 transgender and plural participants. Through thematic analysis, three themes were developed, describing the context of conflict, collective decision-making processes, and solutions that promoted harmony within plural systems. Plural participants were able to effectively navigate decision-making regarding harmful societal narratives about transgender identity, external gender presentation, and receiving gender-affirming medical care. Recommendations from the data serve to assist clinicians in understanding and supporting affirming, autonomous and informed decision-making by trans and plural clients.